Solvent free benzyl alcohol oxidation by AuPd/TiO₂ catalysts - Mohd Jamjam, Norasidah (2017)
The development of gold and palladium as heterogeneous catalyst is widely investigated for many oxidation process. In this respect, the main goal of the research is modification of Au-Pd catalyst to achieve highest potential to obtain more benzaldehyde. The monometallic and bimetallic catalysts are synthesized via impregnation and sol-immobalization methods. The physico-chemical properties of the nanoparticle catalysts are characterized by using X-Ray Diffraction (XRD), X-ray Fluorescene (XRF), Brunauer-Emmett-Teller (BET), Transmission Electron Microscope (TEM), Scanning Electron Microscope (SEM) and Energy Dispersive Spectroscopy (EDS). In addition, the catalytic activity of all synthesized catalysts for the production benzaldehyde by benzyl alcohol with tert-Butyl hydroperoxide (TBHP) as an oxidant and the effect of variables, such as reaction temperature, reaction time, catalyst loading have been evaluated. On the other hand, an examination of the reusability and leaching of gold and palladium into benzyl alcohol is carried out. Among the variables test, the results are discussed with regard to structure activity relationship. The preparation method was shown to be very important in the formation of highly active catalysts. The impregnation method produced catalysts with large Au particles when supported on TiO2 due to large particle size. Preparation of sol-immobilisation methods produced stable catalysts, highly active density of both metal, highest strength, large surface area and selective for the oxidation benzyl alcohol. According to the extensive modification on the catalyst loading on the Au-Pd, the result revealed that 0.5 wt% Au 0.5 wt% Pd/TiO2 catalyst prepared by sol-immobilisation methods showed the best catalytic activity in the oxidation of benzyl alcohol at temperature of 80 ̊C for 4 hours. A synergistic effects of Au-Pd alloys occur on the benzyl alcohol oxidation. It was found that the longer the reaction time, the selectivity of benzaldehyde decrementing and the same was true of highest reaction temperatures (up to 120 ̊C). A good reusability of the catalysts with leaching of gold into the product has also been obtained. Overall, the oxidation of benzyl alcohol was successfully studied by using Au-Pd/TiO2 and the importance of the TBHP as an oxidant is proven in the processes. Moreover, the Au-Pd ratio was the main focus in this study which it is innovated to be a flexible on the current reaction condition with a great performance. These results highlight the advanced of the fundamental understandings of Au-Pd alloys comparing with traditional method in catalyzing benzyl alcohol oxidation.